Novel signatures associated with systemic lupus erythematosus clinical response to IFN-α/-ω inhibition. (April 2021) - Seridi, Loqmane; Cesaroni, Matteo; Orillion, Ashley; Schreiter, Jessica; Chevrier, Marc; Marciniak, Stanley; Migone, Thi-Sau; Stohl, William; Chatham, Walter Winn; Furie, Richard Alan; Benson, Jacqueline; Jordan, Jarrat
Objectives: We aimed to identify transcriptional gene signatures predictive of clinical response, for pharmacodynamic evaluation, and to provide mechanistic insight into JNJ-55920839, a human IgG1κ neutralizing mAb targeting IFN-α/IFN-ω, in participants with systemic lupus erythematosus (SLE). Methods: Blood samples were obtained from SLE participants at baseline and up to Day 130, who received six 10 mg/kg IV doses of JNJ-55920839/placebo every 2 weeks. Participants with mild-to-moderate SLE who achieved clinical responses using SLE Disease Activity Index 2000 Responder Index 4-point change were considered responders. Transcriptional signatures from longitudinally collected blood were generated by RNA-Seq; signatures were generated by microarray from baseline blood samples exposed in vitro to JNJ-55920839 versus untreated. Results: Two gene signatures (IFN-I Signaling and Immunoglobulin Immune Response) exhibited pharmacodynamic changes among JNJ-55920839 responders. The Immunoglobulin signature, but not the IFN-I signature, was elevated at baseline in JNJ-55920839 responders. A gene cluster associated with neutrophil-mediated immunity was reduced at baseline in JNJ-55920839 responders, substantiated by lower neutrophil counts in responders. An IFN-I signature was suppressed by JNJ-55920839 in vitro treatment versus untreated blood to a greater extent in responders before in vivo dosing. Conclusions: These signatures may enable enrichment for treatment responders when using IFN-I-suppressing treatments in SLE.